Characteristics of a negative lightning with multiple‐ground terminations observed by a VHF lightning location system. Issue 1 (14th January 2016) - Sun, Zhuling; Qie, Xiushu; Liu, Mingyuan; Jiang, Rubin; Wang, Zhichao; Zhang, Hongbo
Abstract: Propagation characteristics of a negative cloud‐to‐ground lightning with four leader‐return stroke sequences exhibiting four ground terminations, referred to as multiple termination flash, are analyzed using a two‐dimensional mapping system of lightning radiation sources in VHF band along with broadband electric field change records. The four stepped leader‐stroke sequences were produced from two different branches of the preliminary breakdown process inside the cloud, and the time intervals between each adjacent two leader‐stroke sequences were 82.9 ms, 81.4 ms, and 152.2 ms, respectively. The first two stroke sequences were multiple termination strokes (MTSs), and each MTS showed two different ground terminations induced by two leader branches. The corresponding electric field changes exhibited two fast‐rising waveforms separated by 1.5 ms and 2.7 ms, respectively, and the second peak was 3–4 times smaller than the first. The second grounding branch in each MTS occurred when its channel was in poor connection conditions to the main stroke channel. The third and fourth leader‐stroke sequences connected to the ground with one of the different grounded channels of the second MTS. The dart leaders before these two strokes exhibited chaotic pulse trains (CPTs) with significant slow electric field variations accompanying strong and continuous VHF radiations. The CPTs only occurred in the dart leader stage which propagated with a speed in an order of 10 7 m/s. Different from dart leader, attempted leader was associated with regular pulse trains and propagated at a speed order of 10 6 m/s along the previous channel. Key Points: The multiple termination flash initiated from two channels of preliminary breakdown process The first two strokes exhibit double‐ground terminations produced by two leader branches The CPTs only occurred in dart leader stage when propagating with a speed in an order of 10 7 m/s